EXPERIMENTAL STUDY ON DEVELOPMENT OF ADOLESCENTS' INTERACTION SKILLS IN SOCIAL PAINTING - Barkane, Evita; Truskovska, Zenija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The paper provides an insight into the experimental study on the development of adolescents' interaction skills in social painting that was carried out at Rezekne Academy of Technologies (Latvia) in 2017. The study is part of a broader research conducted from 2015 to 2017.The effectiveness of social painting as a social game and method in development of adolescents' interaction skills in social-pedagogical teamwork is scientifically justified and experimentally validated in the research.